Microbiological Spectrum of Genital Tract Infections in Infertile Women: A Clinical Correlation - Sana Adil, Zunaira Majeed, Ghulam Mustafa, Aliya Zaman, Syeda Nosheen Zehra, Farah Saleem (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Genital tract infections (GTIs) are a major yet preventable cause of female infertility, particularly in regions where late diagnosis, inadequate screening, and asymptomatic infections are common. Understanding the microbiological spectrum and clinical correlations of GTIs is essential for optimizing infertility management. This study aimed to determine the prevalence of reproductive tract pathogens in infertile women and assess their relationship with clinical presentations. Methods: This cross-sectional study was conducted at DHQ Teaching Hospital Mardan, PIMS Hospital Islamabad, and Dr. Faisal Masood Teaching Hospital Sargodha between September 2022 and July 2023. A total of 100 infertile women aged 18–42 years were evaluated. High-vaginal, endocervical, and urethral swabs were collected under aseptic conditions. Microscopy, culture, and PCR assays were used to identify bacterial, fungal, and atypical pathogens. Statistical analysis was performed using SPSS version 26, with a significance threshold of p < 0.05. Results: Pathogens were identified in 73% of participants. The most prevalent organisms were Chlamydia trachomatis (21%), Ureaplasma urealyticum (18%), Gardnerella vaginalis (15%), Candida albicans (14%), and Escherichia coli (11%). Mixed infections were noted in 19% of cases. Vaginal discharge was strongly associated with Gardnerella and Candida, while pelvic pain correlated with Chlamydia and Mycoplasma genitalium. Tubal factor infertility showed a significant association with Chlamydia trachomatis (p = 0.009). Antimicrobial susceptibility patterns indicated high sensitivity of atypical pathogens to doxycycline. Conclusion: GTIs are highly prevalent among infertile women and significantly influence reproductive outcomes. Incorporating routine microbiological screening, including PCR-based diagnostics, into infertility workups is essential for early detection, targeted therapy, and improved fertility prospects. Keywords: infertility, genital tract infections, Chlamydia trachomatis, reproductive microbiology, PCR diagnosis, pelvic inflammatory disease, Ureaplasma urealyticum, bacterial vaginosis, Candida, Pakistan